Contamination of Radioactivity with Uranium and Concentrations of Some Heavy Metals in Human Blood - Hamza , Hala M.; Hussain , Hayder S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This research has been conducted to determine the level of radioactive contamination from uranium and some heavy elements (Pb, Cd, Ni & Cu) in 60 blood samples taken from individuals living in four areas (Ishtar, Jeser Diyala, AL-Wardiya, and Tameem) near the Iraqi Atomic Energy Organization, south of Baghdad, bordered by the Tigris River to the west and the Diyala River to the north. This organization was established in 1967 and was used for legitimate nuclear operations. It was targeted during the Gulf Wars in 1991 and 2003, leading to leaks of containers containing uranium oxides and radioactive sources from the organization to surrounding areas. Living near a nuclear testing site exposes residents to internal and external radiation. The nuclear track detector for solid-state (CR-39) and inductively coupled plasma optical emission spectrometry (ICP-OES) were used to determine the concentrations of uranium and heavy metals. The uranium concentration rates in Ishtar, Jeser Diyala, AL-Wardiya, and Tameem were 0.583±0.02μg/L, 0.546±0.04μg /L,0.439±0.05μg/L and 0.390±0.04μg/L, respectively. Based on the results obtained, it is noticed that the concentrations of uranium in the villages of Ishtar and Jeser Diyala are higher than in the rest of the areas, exceeding the acceptable limit set by the World Health Organization (WHO). The highest concentrations of Pb (0.084 ±0.007) ppm and Cd (0.026 ±0.006) ppm were found in Tameem, the highest concentration of Ni (0.038 ±0.008) ppm in Ishtar, and the highest concentration of Cu (0.168 ±0.033) ppm in Jeser Diyala.